Software for Auto-Generating Electrode Block Order Sheet: Study Case in Mold Machining Workshop - Tetuko Kurniawan; Yosep Purnama (President University, 2016)
In a mold manufacturing process, few to hundreds electrode is required for the EDM process. The electrode production is time consuming and it prone to errors when it comes to creating Electrode Block Order Sheet. New software was developed to create automated process to generated Electrode Block Order Sheet that reduce the time consumption and eliminate human errors during the process. By the application of the software, time consumption to create Electrode Block Order Sheet is reduced by 80% and human error involved in the process is eliminated.Keywords. EDM, mold, software, automation, electrode, manufacture